Practical insights on enzyme stabilization - Silva, Carla (2018)
Enzymes are efficient catalysts designed by nature to work in physiological environments of living systems. The best operational conditions to access and convert substrates at the industrial level are different from nature and normally extreme. Strategies to isolate enzymes from extremophiles can redefine new operational conditions, however not always solving all industrial requirements. The stability of enzymes is therefore a key issue on the implementation of the catalysts in industrial processes which require the use of extreme environments that can undergo enzyme instability. Strategies for enzyme stabilization have been exhaustively reviewed, however they lack a practical approach. This review intends to compile and describe the most used approaches for enzyme stabilization highlighting case studies in a practical point of view.